Investor Risk Behavior as a Mediator in the Influence of Financial Literacy on Millennial Investment Decisions: Evidence from Makassar, Indonesia - Mongan, Claudio Julio; Halik, Johannes Baptista; Lambe, Kristian Hoegh Pride; Irdawati, Irdawati (Journal of Management and Business Review, 2025)
This study examines how investor risk behavior influences the relationship between millennials' investment choices and financial literacy in Makassar, Indonesia. A structured survey with 96 respondents chosen by purposive sampling was used in a quantitative way. The data was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings show that financial literacy has no direct impact on investment choices. Nonetheless, it greatly influences investment decisions by having a considerable favorable impact on investor risk behavior. Additionally, the association between financial literacy and investing decisions is positively mediated by investor risk behavior. These findings indicate that financial knowledge alone is insufficient to induce sensible investment behavior unless integrated with risk tolerance. The study enhances behavioral finance by illustrating the interplay of cognitive and behavioral elements in millennial investing. Practical implications include a need for financial literacy initiatives that combine risk management training to strengthen the ability to make decisions in digital investment environments.